Bone lesions caused by pythium insidiosum in a horse - MENDOZA, L. (1987)
A 5-year-old, female saddle horse developed a tumoral mass anterolaterally on the metacarpal region of its right front leg. Histopathological study showed hyaline, aseptate, broad hyphae in the sequestered coral-like necrotic masses. Radiographs revealed an extensive osteomyelitis with disorganized bone proliferation of the metacarpal bones, as well as exostosis of the distal radius and the proximal and distal row of carpal bones. The etiologic agent was detected histologically, isolated in culture and identified as Pythium insidiosum. Serological tests were positive. Immunotherapy was applied but no cure resulted. The horse was sacrificed and necropsy confirmed the X-ray findings.